Experimental Auction Markets and the Walrasian Hypothesis - Smith, Vernon L. (Journal of Political Economy, 1965)
This study reports on a block of experimental market sessions designed primarily to provide (1) the severest test yet attempted of the equilibrating forces operating in competitive auction markets and (2) a more rigorously controlled test of the Walrasian hypothesis. Some data are also supplied which show the effect of cash payoffs on the equilibrating behavior of such markets; in particular, the effect of full cash payoffs to all successful trading subjects as against payoffs to a subset of such subjects chosen at random.